Extraction-free spectrophotometric determination of meloxicam using bromothymol blue - Donchenko, A. O.; Vasyuk, S. O.; Nahorna, N.; Донченко, Анастасія Олександрівна; Васюк, Світлана Олександрівна; Нагорна, Наталія Олександрівна (My University, 2023)
Objective: The purpose of the present work was to develop and validate a fast, simple and sensitive extraction-free spectrophotometric technique for the quantitative determination of meloxicam based on the reaction with bromothymol blue. Material and Method: The reference standard of meloxicam, bromothymol blue and finished dosage forms of meloxicam were used in the study. Absorption measurements were performed on the Analytic Jena UV-visible spectrophotometer model Specord 200. Result and Discussion: The developed method is based on the formation of the colored reaction product between meloxicam and bromothymol blue in acetone medium with absorption maximum at 348 nm. The method meets the requirements of the State Pharmacopoeia of Ukraine for such validation characteristics as specificity, linearity, precision, accuracy, robustness and range of application. The obedience to Beer's law is observed in the range of meloxicam concentrations 0.80-2.40 mg/100 ml, the correlation coefficient is 0.9998. The range of application of the method is 60-140%.
Keywords: Meloxicam; bromothymol blue; sulfonephthalein dyes; spectrophotometry; validation studies